Collective Vortex-Like Movement of Bacillus subtilis Facilitates the Generation of Floating Biofilms - Steinberg, Nitai; Rosenberg, Gili; Keren-Paz, Alona; Kolodkin-Gal, Ilana (Frontiers in Microbiology, 2018)
Bacteria in nature are usually found in complex multicellular structures, called biofilms. One common form of a biofilm is pellicle—a floating mat of bacteria formed in the water-air interphase. So far, our knowledge on the basic mechanisms underlying the formation of biofilms at air-liquid interfaces is not complete. In particular, the co-occurrence of motile cells and extracellular matrix producers has not been studied. In addition, the potential involvement of chemical communication in pellicle formation remained largely undefined. Our results indicate that vortex-like collective motility by aggregates of motile cells and EPS producers accelerate the formation of floating biofilms. Successful aggregation and migration to the water-air interphase depend on the chemical communication signal autoinducer 2 (AI-2). This ability of bacteria to form a biofilm in a preferable niche ahead of their potential rivals would provide a fitness advantage in the context of inter-species competition.